2005
DOI: 10.1002/mus.20436
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional therapy improves function and complements corticosteroid intervention in mdx mice

Abstract: Corticosteroid therapy for Duchenne muscular dystrophy is effective but associated with long-term side effects. To determine the potential therapeutic benefit from four nutritional compounds (creatine monohydrate, conjugated linoleic acid, ␣-lipoic acid, and ␤-hydroxy-␤-methylbutyrate) alone, in combination, and with corticosteroids (prednisolone), we evaluated the effects on several variables in exercising mdx mice. Outcome measures included grip strength, rotarod performance, serum creatine kinase levels, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 55 publications
(113 reference statements)
2
60
1
Order By: Relevance
“…In this context, protocols based on different drugs, genes, and cells have been proposed to counteract muscle derangement, [2][3][4] and nutritional supplements have been considered in the attempt to increase muscle strength and prevent myocyte catabolism [5][6][7] or to decrease corticosteroid side effects. 8 3 and 6 polyunsaturated fatty acids (PUFAs) are metabolically and functionally distinct and often have opposing physiological effects. Mammals depend on dietary intake of 3 fatty acids through vegetable sources or fish oil because their cells lack enzymes necessary to synthesize the 18-C precursor of 3 fatty acids and to introduce a double bond at the 3 and 6 position.…”
mentioning
confidence: 99%
“…In this context, protocols based on different drugs, genes, and cells have been proposed to counteract muscle derangement, [2][3][4] and nutritional supplements have been considered in the attempt to increase muscle strength and prevent myocyte catabolism [5][6][7] or to decrease corticosteroid side effects. 8 3 and 6 polyunsaturated fatty acids (PUFAs) are metabolically and functionally distinct and often have opposing physiological effects. Mammals depend on dietary intake of 3 fatty acids through vegetable sources or fish oil because their cells lack enzymes necessary to synthesize the 18-C precursor of 3 fatty acids and to introduce a double bond at the 3 and 6 position.…”
mentioning
confidence: 99%
“…56 Finally, a combination of creatine monohydrate, conjugated linoleic acid, alpha-lipoic acid and betahydroxy-beta-methylbutyrate (HMB) improved strength and decreased fatigue in the mdx mouse. 57 This combination was better than any individual supplement alone as well as prednisone alone, although all had some benefit. The combination with prednisone provided the best results.…”
Section: Supplementsmentioning
confidence: 94%
“…Other supplements (creatine monohydrate, conjugated linoleic acid, alpha-lipoic acid, and beta-hydroxy-beta-methylbutyrate) when given in combinations, were found to improve strength in the mdx mouse, with greatest efficacy in combination with prednisone [83]. Oral creatine supplementation alone showed efficacy in trials in mdx mice but demonstrated no beneficial effects on strength and function in patients with DMD [84][85][86].…”
Section: Nutritionalmentioning
confidence: 99%